The changing composition of imports of highly indebted countries - Jesko Hentschel (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1989)
A number of highly indebted developing countries have experienced severe foreign exchange shortages for a couple of years. They could not simply roll over old debt any more by taking up new loans. Since export revenues could not be raised sufficiently, quite a few countries resorted to a curtailment of imports. This paper examines whether the cutback on imports was distributed equally across different types of import goods for a number of countries classified as being problem debtors. It can be observed that the cutback fell primarily on capital goods. In addition, capital goods produced abroad accounted for a significantly smaller share in total Gross Fixed Capital Formation after the outbreak of the debt crisis than before. Consumption goods also carried the burden of adjustment, but only if they accounted for a substantial share of imports before the beginning of the crisis. The share of intermediate goods in real merchandise imports increased instead, reflecting the short-run vulnerability of domestic output to imported inputs.
Keywords: 330